Comportamento do consumidor de alimentos orgânicos na cidade de Uberlândia: um estudo com base na cadeia de meios e fins - Pimenta, Márcio Lopes (2008)
The national and international organic market has been showing an expressive rising over the last ten years. It justifies the increasing in the Brazilian agricultural areas that are dedicated to the organic production system, and consequently of the channel members that conduct these products to the final consumer. This environment highlights the importance of knowing the behavior of the consumer of organic food, in the aim of guiding the marketing efforts and consequently modeling the production systems toward a market orientation of the firms. Inside a supermarket-retailer context, this research aims to describe the characteristics of the consumer s behavior of organic fruit and vegetables in Uberlândia, Minas Gerais. More specifically, it aimed to evidence this behavior based upon the perceived product attributes by the consumers, on the consequences (benefits) that these attributes are able to provide and on the connection of these two elements with personal values. Based upon a technique named laddering, that uses the means end chain theory assumptions, thirty interviews were conducted with persons who had consumed organic fruit and vegetables in two supermarkets of Uberlândia, between August and November of 2007. This technique provided the building of an implication matrix and a hierarchical value map, which allowed to show the elements that characterize such behavior. The results reveal in an emphatic way, a concern for the individual well being and for its maintenance over the time, through life quality and a healthy life, classified as individual values according the Schwartz scale. It was evidenced the possibility of reaching these values through many ways, that is, through chains with different attributes and consequences. These chains are commenced by the attributes: absence of chemical products, sensorial characteristics (taste, smell and color), more concentrated, more nutritious, less perishability, quality and, dirty /unattractive. There is, however, with less emphasis, the wish for values such as: nostalgia, human valorization and time to get other things done, which are possible owing to the attribute absence of chemical products. Finally, propositions are presented to show the dominant perceptions about values of these consumers, based upon the enchainment of the elements identified above.